Of Aging Mice and Men: Gait Speed Decline Is a Translatable Trait, With Species-Specific Underlying Properties. (14th January 2019) - Bair, Woei-Nan; Petr, Michael; Alfaras, Irene; Mitchell, Sarah J; Bernier, Michel; Ferrucci, Luigi; Studenski, Stephanie A; De Cabo, Rafael
Abstract: In the last two decades, great strides were made in our ability to extend the life span of model organisms through dietary and other manipulations. Survival curves provide evidence of altered aging processes but are uninformative on what lead to that increase in life span. Longitudinal assessments of health and function during intervention studies could help in the identification of predictive biomarkers for health and survival. Comparable biomarkers of healthspan are necessary to effectively translate interventions into human clinical trials. Gait speed is a well-established predictive biomarker of healthspan in humans for risk of disability, health outcomes and mortality, and is relatively simple to assess noninvasively in rodents. In this study, we assessed and compared gait speed in males from two species (mice and humans), from young adulthood to advanced old age. Although gait speed decreases nonlinearly with age in both species, the underlying drivers of this change in gait speed were different, with humans exhibiting a shortened step length, and mice displaying a decrease in cadence. Future longitudinal and interventional studies in mice should examine the predictive value of longitudinal declines in gait speed for health and survival.